1971
DOI: 10.1136/bmj.3.5769.279
|View full text |Cite
|
Sign up to set email alerts
|

Vesico-ureteric Reflux after Renal Transplantation

Abstract: BRITISH MEDICAL JOURNAL 31 JULY 1971 279 that prostaglandin E2 is more effective in inducing labour must be considered with caution, for though the patients were selected at random the groups were not identically matched. The differences found in these studies may be partly explained by essential differences in the plan of each investigation and the exact protocol undertaken. Beazley and Gillespie (1971) started the infusion of prostaglandin E, at 0-21 [Lg/min and oxytocin at 2 1 mU/min. These rates were dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Spon taneous healing of ureteric fistulas has also been described after temporary nephrostomy [7,9,10]. Whether open 84 Dreikorn Problems of the Distal Ureter in Renal Transplantation surgery is necessary primarily depends on the status of the graft ureter. In case of extensive ureteral necrosis conser vative management alone will hardly be successful.…”
Section: Diagnosis and Management O F Ureteric Complicationsmentioning
confidence: 99%
“…Spon taneous healing of ureteric fistulas has also been described after temporary nephrostomy [7,9,10]. Whether open 84 Dreikorn Problems of the Distal Ureter in Renal Transplantation surgery is necessary primarily depends on the status of the graft ureter. In case of extensive ureteral necrosis conser vative management alone will hardly be successful.…”
Section: Diagnosis and Management O F Ureteric Complicationsmentioning
confidence: 99%
“…The investigations of Powis, Barnes and Dawson Edwards (1971) showed that 8 out of 18 cases reiluxed followiiig a tunnel type of re-implantation and perhaps suggested that there may be a special problem associated with ureteric re-implantations fo!lowing transplantation. However our studies do not support such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal Infirmary, Cardif -THE ureteric complications of renal transplantation have been discussed at length in several recent papers by Owen (1972), Rees (1972) and Robson and Calne (1971). There has been a review of ureterovesical competence following renal transplantation by Powis, Barnes and Dawson Edwards (1971).…”
Section: Vesico-ureteric Reflux After Renal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…cesophagitis, diverticulitus (Fig 5), steatorrhcea) is approximately the same (Hadjiyannakis et al 1971). Ileocolonic ulceration has occurred at any time up to 18 months after transplantation (Powis et al 1971).…”
mentioning
confidence: 83%